2022
DOI: 10.1002/stc.3140
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical analysis on the measurement accuracy of embedded strain sensor in asphalt pavement dynamic response monitoring based on FEM

Abstract: Embedded strain sensors are the primary measurement device for strain in the tensile layer of asphalt pavement. The favorable deformation compatibility between embedded strain sensor and asphalt layer is the key to ensure the precise measurement of mechanical response. However, the good deformation coordination may be difficult to maintain under different environments due to the viscoelasticity of asphalt mixture. In this study, 4-point bending beam tests were performed to investigate deformation compatibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Te selection and reliability verifcation of sensors have been mentioned in previous studies [46][47][48]. Under the center of the wheel track, longitudinal, lateral, and vertical asphalt strain gauges were embedded in the middle and bottom asphalt surface layers [49,50]. Longitudinal and lateral concrete strain gauges were embedded in the bottom of the base layer.…”
Section: Experiments Designmentioning
confidence: 99%
“…Te selection and reliability verifcation of sensors have been mentioned in previous studies [46][47][48]. Under the center of the wheel track, longitudinal, lateral, and vertical asphalt strain gauges were embedded in the middle and bottom asphalt surface layers [49,50]. Longitudinal and lateral concrete strain gauges were embedded in the bottom of the base layer.…”
Section: Experiments Designmentioning
confidence: 99%
“…The outputs of these three FBG sensors were 0.89, 1.65, and 8.64 times the actual deformation of the asphalt mixture, respectively. Han et al [14] studied the agreement between the output of the embedded sensors and the deformation of asphalt mixtures through laboratory tests. The experimental results showed that the embedded strain sensor exhibits more significant errors at higher temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Han et al [17] studied the deformation compatibility between the embedded strain sensor and asphalt layer, concluding that it is the key to ensuring the precise measurement of mechanical response. However, good deformation coordination may be difficult to maintain under different environments due to the viscoelasticity of asphalt mixture.…”
Section: Introductionmentioning
confidence: 99%